Reader Self-Efficacy in Relation to the Reading Comprehension of Students with Special Nedds in an Inclusive Education Setting - Quinto, Diana France (Archīum Ateneo, 2019)
This study explored the relationship between the dimensions of reader self- efficacy and the reading comprehension of students with special needs in an inclusive education setting. In this study, the Reader Self-Perception Scale (Henk & Melnick, 1995) and the Informal Reading Inventory from McGraw-Hill Reading Wonders Program were administered to 22 Grades 4-6 students under the Center for Individualized Academic Programs (CIAP) Department. Results of the descriptive statistics and Spearman Correlation coefficient found no significant relationship between the factors of reader self-efficacy and reading comprehension. Although the results were not significant, a moderately positive correlation was seen at a significance level of 0.05 between reading comprehension and Progress (r = .42, p <0 .06). This implies that further studies regarding the relationship between reader self- efficacy and reading comprehension may be necessary due to varying results.